How sleep matters: associations of sleep with negative affect, health perceptions, and cognitive performance in older adults’ daily lives - Lücke, Anna J. (2022)
Sleep is crucial for well-being, health, and cognitive functioning both from day-to-day and in the long-term. Because older adults experience declines in health and cognitive functioning as well as changes in sleep characteristics it is especially important to understand the interplay between sleep and daily well-being and functioning in this age group. The distinction between sleep quality and sleep duration should also be considered as their associations with daily functioning may differ. Using a broad theoretical approach to daily functioning, I thus examined daily associations of sleep quality and sleep duration with affective, health-related, and cognitive functioning in old and very old age. In this dissertation, I used data from two seven-day experience sampling studies with young-old and old-old adults. In addition to reporting on their sleep quality and sleep duration each morning, participants rated their current emotions and stress experiences, reported their momentary health and pain, and participated in two trials of a working memory task six times per day. Using these data, I first tested theoretical predictions that sleep is linked with affective stress reactivity rather than negative affect per se. Multilevel structural equation models (SEM) based on data from 325 older adults showed that after nights with lower sleep quality people reported more stressor-unrelated negative affect but not stronger stress reactivity the next day. However, when people experienced increased stress reactivity during the day, they reported lower sleep quality the following night. Sleep duration was not significantly linked with affective experiences. Second, I aimed to clarify the previously indeterminate temporal direction of associations between sleep and health perceptions. Partially confirming the predictions, results from dynamic SEM based on data from 170 older adults showed that when participants slept better than usual, they reported less pain and increased self-rated health the next day. Sleeping longer was not linked with either pain or self-rated health. Regarding the reversed direction, on days when people rated their health better, they slept better, but not longer, the next night. Third, I examined links of sleep with initial levels, learning improvements, and variability in working memory across a week and analyzed whether variations in sleep and working memory were linked from day to day. Results from multilevel location-scale models based on data from 160 older adults showed that people who slept longer and people who slept shorter than the sample average showed lower initial performance levels, but a stronger increase of working memory performance over time (i.e., larger learning effects), relative to people with average sleep duration. Sleep duration did not predict performance variability over one week. Sleeping shorter than usual was only linked with worse next-day working memory performance for people with short average sleep durations. Individual differences in sleep quality were not significantly associated with initial performance levels, learning effects, or variability of working memory in daily life. The associations between sleep and daily functioning did not systematically differ with participants’ age. Finally, I integrate the results for the different areas of daily functioning, consider the strengths and limitations of the current research, and give an outlook of avenues for future research, including suggestions for interventions. In summary, the results from my dissertation underline that sleep is highly relevant for daily functioning in old age, and that it is important to distinguish between sleep quality and sleep duration. The results suggest a critical role of sleep quality for affective well-being and health perceptions, whereas sleep duration may be more important for cognitive performance. Overall, sleep may be a promising target for interventions to improve older adults’ daily lives.